2019
DOI: 10.21608/bvmj.2019.13806.1022
|View full text |Cite
|
Sign up to set email alerts
|

The potential anti-inflammatory effect of Omega-3 polyunsaturated fatty acids on experimentally induced ulcerative colitis in rats

Abstract: Ulcerative Colitis (UC) is one of the major inflammatory Bowel Syndrome which shows incremental incidence worldwide, with particular occurrence in North America and Middle East. In the present study, the potential protective and curative effects and the molecular mechanisms of Omega-3 polyunsaturated fatty acids (ω-3PUFAs) in rat model of acetic acidinduced UC were investigated. Forty male albino rats were divided into five equal groups. Group I: (Control group) rats received no drugs. Group II: (Early UC-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
1
Order By: Relevance
“…The results showed that after administration of n-3PUFAs, the expression levels of IL-1 and Caspase-3 were downregulated, whereas Bcl-2 was upregulated. These findings imply that n-3 PUFAs protect the colonic mucosa of rats against acetic acid-induced UC, and may aid in the repair of UC via anti-inflammatory and anti-apoptotic properties, as well as a regenerative endogenous antioxidant mechanism ( 307 ).…”
Section: Selected Components Of the Mediterranean Diet And Their Effe...mentioning
confidence: 97%
“…The results showed that after administration of n-3PUFAs, the expression levels of IL-1 and Caspase-3 were downregulated, whereas Bcl-2 was upregulated. These findings imply that n-3 PUFAs protect the colonic mucosa of rats against acetic acid-induced UC, and may aid in the repair of UC via anti-inflammatory and anti-apoptotic properties, as well as a regenerative endogenous antioxidant mechanism ( 307 ).…”
Section: Selected Components Of the Mediterranean Diet And Their Effe...mentioning
confidence: 97%
“…Цитокины продуцируются широким кругом клеток, включая моноциты и макрофаги, Т-лимфоциты, В-лимфоциты и тучные клетки, а также другие типы клеток, такие как эндотелиальные, фибробласты и адипоциты. Цитокины ассоциируются с воспалительными заболеваниями, при этом более высокий уровень ФНО, IL-1β, IL-6 и IL-8 является общим признаком многих воспалительных состояний [23][24][25]. Экспериментальные исследования показали, что ЭПК и ДГК подавляли стимулированную бактериальными эндотоксинами продукцию провоспалительных цитокинов IL-6 и IL-8 культивируемыми клетками эндотелия человека [34,35,[45][46][47][48], тогда как ЭПК подавляли индуцированную эндотоксинами продукцию TNF культивируемыми моноцитами [31][32][33].…”
Section: омега-3 жирные кислоты и цитокиныunclassified